PENERAPAN PENDEKATAN SCIENTIFIC UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII MTsN PALU BARAT PADA MATERI KELILING DAN LUAS DAERAH LAYANG-LAYANG - Efriana, Fanny (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
This study aims to obtain a description of the application of scientific approaches that can improve student learning outcomes of class VII MTsN West Palu on the material and the area around the kite. This research is a classroom action research. The research design refers to the design of research Kemmis and Mc. Taggart, namely planning, action and observation, and reflection. The results showed that the application of a scientific approach can improve learning outcomes in the material and the area around the kite with the following steps: (1) observing, (2) questioning, (3) associating, (4) experimenting, (5) networking. .